PENGARUAH KEMAMPUAN INTELEKTUALITAS DAN MORALITAS TERHADAP TINGKAT KESUKSESAN DALAM PENGEMBANGAN KARIER KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PADANG - Syahril Syahril (Menara Ilmu, 2020)
Abstract : Based on data obtained from the PDAM (Padang Municipal Water Supply Company), that the ability of intellectual and morality determines the level of success in the career development of employees in the PDAM (Regional Drinking Water Company) of the City of Padang. Intellectual ability possessed by the employee will show the work procedures that are systematic and accurate, as well as the morale owned by this employee will determine the behavior of employees at work, because if employees have no intellectual ability and immoral, the level of success is difficult to achieve, while the PDAM (Regional Drinking Water Company) is a community owned so its employees must be demanded to have intellectual abilities and have good morals in accordance with the demands of the community, especially the people in the city of Padang.From the description of the background above, the main problem in this study is "How much is the ability of intellectual and morality to have significantly influence the level of success of the Career Development of Padang City's Municipal Water Company (PDAM). "The purpose of this study was to determine the effect of intellectual ability and morality on the level of success in developing the employees of the PDAM (Drinking Water Company) in the city of Padang. Intellectuality significantly and positively influences the level of success in the career development of Padang City PDAM (Regional Water Company) employees partially. Likewise morality has a significant and positive effect on the level of success in the career development of Padang City's PDAM (Daereah Air Drinking Company) employees also partially. Furthermore, intellectual ability and morality have a significant and positive effect on the level of success in the career development of Padang City's PDAM (Regional Drinking Water Company) simultaneously. The collection method in this study was carried out by distributing questionnaires to all respondents in this case the employees of the PDAM (Regional Drinking Water Company) of the city of Padang. To analyze the effect of intellectual ability and morality on the level of success in the career development of PDAM Kota Padang Regional Water Company employees is to use multiple linear regression equations. From the analysis results obtained by the equation Y’= a + b_1 X_1 + b_2 X_2. The purpose of this multiple regression analysis is to examine how much the level of intellectuality and morality has a significant effect on the level of success in the career development of employees of the PDAM (Municipal Water Company) of the city of Padang. Furthermore also tested how closely the relationship of intellectual ability and morality to the level of success in the career development of employees of the PDAM (Regional Drinking Water Company) of the city of Padang. While the population in this study were all PDAM (Regional Water Company) employees, totaling 41 people. While the sample is 41 people also using total sampling techniques. It is expected that all employees can improve their intellectual abilities and morality so that the level of success can be achieved properly. Keywords: Intellectual Ability, Morality, Success and Career Level